Controle químico de Pteridium arachnoideum em pastagens do médio norte Matogrossense - Ducatti, Kassia Renostro (2016)
This study aimed to evaluate the chemical control of bracken fern (Pteridium arachnoideum) by applying 2,4-D + picloram (Tordon®) and metsulfuron-methyl (Ally®), in isolation or combination of both herbicides applied in two ways: on intact vegetation (foliar application) or immediately after cutting and removal of leaf blades. It was tested two concentrations of each formulated product and a control without application in a completely randomized design with three replications. The experimental units consisted of bracken fern foci with good vegetative vigor and average area of 3:54m2 . The applications were performed with manual backpack sprayer, with conical nozzle type until wetness (moisten) point for foliar applications and volume equivalent to the cut areas. All treatments had excellent efficacy in controlling bracken until the previous evaluation up to 90 days after herbicide application, with faster action in those containing metsulfuron-methyl. At 90 days of the treatments application there was residual action of all herbicides, characterized by drying and death of new shoots that emerged in the applied area